PTH-127 The lived experiences of British South Asian women with Inflammatory Bowel Disease: A qualitative study. (June 2019) - Ford, Angela; Paniagua, Hiliary; Brookes, Matthew; Steed, Helen; Purewal, Satvinder
Abstract : Introduction: The rates of inflammatory bowel disease (IBD) amongst the British South Asian (SA) populations is growing, with some evidence indicating British SA are disproportionally more likely to suffer from IBD than White European. There is a limited understanding of the experience of SA women with IBD, where high rates of infertility, voluntary childlessness and fewer children are common compared to the general population. The objective of this study is to explore how South Asian women with IBD experience living with their chronic illness within dominant SA culture, where childbearing and parenthood are considered culturally mandatory. Methods: A qualitative methodology was adopted using Critical Discursive Psychology (CDP). A total of eight SA women, aged between 19–50, were recruited through two IBD clinics in West Midlands hospitals. Unstructured one to one interviews were audio recorded and analysed using CDP methods. Results: Data analysis revealed that SA culture and IBD is seen as a hindrance to female worth, marriage and parenthood prospects. Further, there is a limited awareness of IBD that leads to secrecy and stigmatisation. Many SA women find coping with IBD difficult due to the perceived stigma regarding IBD and 'disease', lack of understanding about IBD (by patients before diagnosis, family and wider community), pressures regarding cultural mandatory marriage and parenthood, and the role of food (particularly spicy food) in health and illness. Conclusion: This study has shown how IBD in SA women create significant personal and social challenges, which deviates from normative expectations of women in this community. It has raised awareness of the emotional and social impact of IBD, which is critical for service provision that suitably meets the needs of this population. This study has highlighted the need for sensitive and culturally-appropriate intervention for SA patients with IBD.